Polícia! para quem precisa de justiça : como a magistratura representa a violência policial - Muniz, Mariana Py, (2021)
It is questioned what is the social representation of police violence for the State Magistracy of RS. What is considered lawful or not, given the mandate for the use of force for the police, due to the monopoly on the exercise of violence by the State, as well as what implications are drawn from the meaning given to this social phenomenon. Therefore, we justify the choice of the theme due to professional experience developed in front of the coordination of the Human Rights Reference Center of the Public Defender of RS. We assume that police violence is a structural and institutionalized phenomenon. With Lima, we reinforce the observation that the police work with a hierarchical concept of culture when classifying the population under surveillance, which the legal, official and unofficial ideology supports. Through the theory of social representations, we intend to verify how the Judiciary contributes to the construction of the social. With Bourdieu we intend to unveil this legal and judicial field, as well as, based on his propositions, we intend to demonstrate that police violence in Brazil, as it is incorporated into the regulatory structures of repression (Holloway), constitutes a structuring structure of Brazilian society itself and the legal field. Afterwards, we want to move through the structuring of the Judiciary, composition and training, as well as its inquisitorial characteristics, which reproduce hierarchization, inequality, conservatism, with this Power approaching the representation given by common sense to police violence, with its consequent legitimation. We aim to verify how the Judiciary has acted on this theme, which is why the methodology will include bibliographic, documentary and jurisprudential review, analysis of judicial decisions, in addition to the collection of empirical data, with participant observation and application of semi-structured interviews.